Kinetics of methane production during anaerobic digestion of chicken manure with sawdust and miscanthus. (December 2020) - Pečar, Darja; Goršek, Andreja
Abstract: Anaerobic digestion is one of the sustainable processes for biogas production, especially if some of the classic substrate is replaced with lignocellulosic biomass. The presence of lignin makes plant biomass degradation less efficient. Lignin mineralization is an enzyme-dependent process catalyzed by complex ligninolytic enzymes which are produced by white-rot fungi. In our study Pleurotus ostreatus and Trametes versicolor fungi were selected for pre-treatment of Miscanthus which was used as a co-substrate in anerobic digestion. Anaerobic digestion was performed once with ordinary Miscanthus and then with fungi pre-treated Miscanthus. Different process parameters were tested; chicken manure with sawdust and Miscanthus mass ratio (80:20, 60:40, 50:50) and process temperature (35, 40, 42)°C. The volume of biogas produced and the concentration of methane were measured over 21 days. The maximum obtained concentration of methane in the resulting biogas varied between 51% and 58.73% under all different conditions. We have clearly shown that the rate of lignin degradation and consequently the methane productivity are not necessarily improved by fungi pre-treatment. Nevertheless, digestion kinetics is important for designing digesters and predicting the behavior of anaerobic systems. Kinetic parameters of anaerobic digestion of chicken manure with sawdust and ordinary Miscanthus or pre-treated Miscanthus were determined. Graphical abstract: Image 1 Highlights: Miscanthus was used as co-substrate in anaerobic digestion of chicken manure with sawdust. Pleurotus ostreatus and Trametes versicolor are not capable to delignify Miscanthus. Complete kinetic study of selected anaerobic digestion was conducted. Mixture mass ratio and digestion temperature have an effect on methane production.